2005
DOI: 10.1007/s11274-004-5488-7
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of naringinase from a newly isolated strain of Aspergillus niger 1344 for the transformation of flavonoids

Abstract: An extracellular naringinase (an enzyme complex consisting of a-L-rhamnosidase and b-D-glucosidase activity, EC 3.2.1.40) that hydrolyses naringin (a trihydroxy flavonoid) for the production of rhamnose and glucose was purified from the culture filtrate of Aspergillus niger 1344. The enzyme was purified 38-fold by ammonium sulphate precipitation, ion exchange and gel filtration chromatography with an overall recovery of 19% with a specific activity of 867 units per mg of protein. The molecular mass of the puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 25 publications
8
60
3
1
Order By: Relevance
“…Palmyrah Fruit Pulp at 37 o C for 72 hours which showed its optimum activity at 50 o C and at pH 4.0 (Puri and Kalra, 2005). The stability was determined at low temperature (37 o C) but in the present study, stability was determined at 60 o C. The enzyme activity is influenced by different factors such as temperature, pH, substrate concentration, enzyme concentration, inhibitors, metal ions and incubation period.…”
Section: Karuppaija Et Al Kinetic Properties Of Extracellular Thermomentioning
confidence: 66%
See 1 more Smart Citation
“…Palmyrah Fruit Pulp at 37 o C for 72 hours which showed its optimum activity at 50 o C and at pH 4.0 (Puri and Kalra, 2005). The stability was determined at low temperature (37 o C) but in the present study, stability was determined at 60 o C. The enzyme activity is influenced by different factors such as temperature, pH, substrate concentration, enzyme concentration, inhibitors, metal ions and incubation period.…”
Section: Karuppaija Et Al Kinetic Properties Of Extracellular Thermomentioning
confidence: 66%
“…When Rhizophus stolonifer strain was grown in the solid state fermentation system using paddy husk as media, naringinase production was higher (269.84 U/gram of dry substrate) in seven days (Karuppaija et al, 2016b). The activity of the crude naringinase obtained from this strain was maximum at 65 o C. Activity of naringinase from Aspergillus flavus and Aspergillus niger were optimum at 50 o C (Radhakrishnan andSampath, 2013 andPuri andKalra, 2005). Another study indicates that the activity of crude naringinase from Aspergillus niger and Penicillium decumbens were optimum at 55 o C (Norouzian et al, 2000 andThammawat et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The purified enzyme having the optimum pH in the neutral pH range is more suitable for the enhancement of wine aroma (Yadav et al, 2012). The α-L-rhamnosidases reported from Curvularia lunata (Feng et al, 2007), Aspergillus niger (Puri and Kalra, 2005) and Aspergillus kawachii (Koseki et al, 2008) have same optimum pH i.e., 4. Yanai and Sato (2000) reported that the enzyme from yeast Pichia angusta showed an optimum activity at pH 6.…”
Section: Enzyme Characteristics Effect Of Ph On the Activity Of Purifmentioning
confidence: 99%
“…The optimum temperature obtained was similar to the α-L-rhamnosidases from Bacillus sp. GL1 (Hashimoto et al, 1999), Lactobacillus plantarum NCC 245 (Avila et al, 2009), Aspergillus flavus (Scaroni et al, 2002), Curvularia lunata (Feng et al, 2007), Aspergillus niger (Puri and Kalra, 2005) and Aspergillus kawachii (Koseki et al, 2008). Enzymes from Pichia angusta (Yanai and Sato, 2000), Aspergillus kawachii, Penicillium aureatiogriseum and Trichoderma longibrachiatu (Scaroni et al, 2002) were optimally active at 40°C and 60°C.…”
Section: Enzyme Characteristics Effect Of Ph On the Activity Of Purifmentioning
confidence: 99%
See 1 more Smart Citation